SUPPRESSING DIFFRACTION EFFECT USING KIRCHHOFF PRE-STACK TIME MIGRATION ON 2D SEISMIC MULTICHANNEL DATA AT FLORES SEA - Tumpal Benhard Nainggolan; Subarsyah Subarsyah (Marine Geological Institute of Indonesia, 2014)
2D seismic multichannel survey has been carried out by Marine Geological Institute of Indonesia to interpret imaging and sub-surface geological information in the Flores Sea. Seismic data processing starts from pre-processing until migration stage. Migration is an important stage in the seismic processing, because at this stage the effects of diffraction and oblique reflectors caused by fault, salt domes, wedging, etc. will be repositioned to the actual points. One example of diffraction effects can be seen on the seismic section of a conventional stacking that have not migrated, i.e. resulting in an apparent bowtie reflector. Geologists find difficulties in interpreting geological information from diffracted seismic section, so it needs further processing to overcome the effects. By using Kirchhoff method and carried out during the Pre-Stack Time Migration (PSTM), this method turns out to produce migrated seismic section which is much better than conventional stacked one. This is due to the Kirchhoff method suppressed the identified diffraction effects, so that the geologist can interpret geological structure of the resulting migrated seismic section of the Flores Sea. Keywords : 2D seismic multichannel, diffraction, Pre-Stack Time Migration (PSTM), Kirchhoff method. A Survei seismik 2D multichannel dilaksanakan oleh Marine Geological Institute of Indonesia untuk mengetahui gambaran serta informasi geologi bawah permukaan Laut Flores. Pengolahan data seismik dimulai dari pre-processing sampai tahap migration. Tahap migration merupakan tahap terpenting dalam pengolahan data seismik, oleh karena pada tahap ini efek difraksi dan reflektor miring yang diakibatkan oleh sesar, kubah garam, pembajian, dan lain-lain akan dikembalikan pada keadaan sebenarnya. Salah satu contoh adanya efek difraksi bisa dilihat pada penampang stacking konvensional yaitu â€œbowtieâ€ yang mengakibatkan terjadinya reflektor semu pada penampang seismik. Efek difraksi â€œbowtieâ€ sangat menyulitkan para peneliti dalam memperoleh informasi geologi, sehingga perlu adanya proses lebih lanjut untuk mengatasi efek tersebut. Salah satu metode migrasi yang berkembang saat ini yaitu metode Kirchhoff dan dilakukan pada saat Pre-Stack Time Migration (PSTM), menunjukkan hasil penampang jauh lebih baik daripada penampang stacking konvensional. Hal ini terjadi karena pada metode Kirchhoff Pre-Stack Time Migration, efek difraksi tersebut ditekan lebih awal sehingga penampang yang dihasilkan mampu menggambarkan struktur geologi permukaan Laut Flores Sea. Kata kunci : seismik 2D multikanal, difraksi, Pre-Stack Time Migration (PSTM), metode Kirchhoff.